How are signed languages learned as second languages?. Issue 1 (4th December 2020) - Marshall, Chloe; Bel, Aurora; Gulamani, Sannah; Morgan, Gary
Abstract: This review addresses the question: How are signed languages learned by adult hearing learners? While there has been much research on second language learners of spoken languages, there has been far less work in signed languages. Comparing sign and spoken second language acquisition allows us to investigate whether learning patterns are general (across the visual and oral modalities) or specific (in only one of the modalities), and hence furthers our understanding of second‐language acquisition (SLA). The paper integrates current sign language learning research into the wider field of SLA by focussing on two areas: (1) Does 'transfer' occur between the spoken first language and signed second language and (2) What kind of learning patterns are the same across language modalities versus unique to each modality?